Determinants of Information and Communication Technology Development in Indonesia (2018-2021) - Saputra, Arga Bayu; Artaningtyas, Wahyu Dwi (Journal of International Conference Proceedings, 2023)
This study aims to analyze the influence of average household consumption for telecommunications, households that own and control cell phones, Number of Villages or Regions Receiving Cell Phone Signals and the Covid-19 Pandemic on the Information and Communication Technology Development Index in Indonesia for 2018-2021. The data used in this study is secondary data, namely the Information and Communication Technology Development Index, Average Household Consumption for Telecommunications, Households Who Own and Control Cell Phones, Number of Villages/Regions That Receive Cell Phone Signals and the Covid-19 Pandemic as dummy variables, which have been published by the Indonesian Central Bureau of Statistics. The analytical method used in this study is panel data regression analysis using the Fixed Effect Model approach. The study results show that variablesAverage Household Consumption for Telecommunications, the variable Households Who Own and Control a Cellular Telephone have an influence, the variable Number of Villages/Regions Receiving Cellular Telephone Signals and Communication and the Covid-19 Pandemic variable have a positive and significant influence on the variableInformation and Communication Technology Development Index in Indonesia 2018-2021.